The Arizona diary of Lily Frémont, 1878-1881 - Frémont, Lily, 1842-1919 (University of Arizona Press, 1997)
On a more personal level, the reader will find intimate accounts of John Fremont's obsession with mining promotion, his complicated business dealings with Judge Silent, and his attempts to recoup his family's sagging fortune. Here especially, Lily outlines a telling profile of her father, a man roundly castigated then and now as a carpetbagger less interested in promoting Arizona's interests than his own. For students of western history, Lily Fremont's diary provides a wealth of fresh information on frontier politics, mining, army life, social customs, and ethnicity.